Reflexão sobre os méritos de Maria em vista de sua maternidade divina - Siles, Alexandre Augusto (2018)
This dissertation proposes to highlight the merits of the Virgin Mary in the life of the People of God and of the Church, from her divine motherhood. However, it is a fact that there was a way to be followed so that Mary could receive the title of Mother of God and intercessor, above all, from the birth of the Church on Mount Calvary, where on the cross, Jesus gives her as Mother of the faithful disciple (John 19:26). Thus, emphasizing Christology in the life of Mary and with a look from a Marian perspective, I propose a small reflection on the benefits that the Mother of Jesus received because of the merits of her divine motherhood (LG 53). In fact, Mary also has a special place in the life and heart of the little ones, since according to the Gospel of Luke they will call her by all generations of blessed (Lk 1:48). Thus, to speak of Marian merits and intercession is an immense pleasure, for Jesus will always be at the center of every theme, and at the same time to mark Marian traits in the history of Jesus of Nazareth is a great ecclesial and pastoral challenge. Faults of communication, because it is from Jesus that all salvation comes, and it is from Mary that the Savior is born